Fuzzy Kano Integrated MCDM Approach for Supplier Selection Based on Must Be Criteria - Naveen Jain; A. R. Singh (International Journal of Supply Chain Management, 2017)
Globalization of markets has compelled the industries to adopt new strategies of business to sustain in competitive markets. Therefore, industries are adopting innovative methods for selection of supply chain partners. Criteria of supplier selection should be based on industry need and type of product. In this work philosophy of Kano model has been applied for classification of criteria into different sets. Fuzzification of Kano model overcomes the constraint of single response and allows respondent to express customer satisfaction feelings in form of multiple numeric values. In this work decision makers categorized thirty-six criteria in to different sets and Must Be criteria are identified for supplier selection process. Further, Step-wise Weight Assessment Ratio Analysis (SWARA) method and Range of Values (ROV) method has been applied for weight assignment of criteria and ranking of alternatives respectively. Researchers and industrial practitioners can apply this methodology to other industries by choosing a different set of criteria.Keywords Supplier Selection, Selection Criteria, SWARA, ROV, Fuzzy Kano Model, MCDM